Targeting Fibroblast Growth Factor 23 Signaling with Antibodies and Inhibitors, Is There a Rationale? - Fukumoto, Seiji (Frontiers in Endocrinology, 2018)
FGF23 is a phosphotropic hormone mainly produced by bone. FGF23 reduces serum phosphate by suppressing intestinal phosphate absorption through reducing 1,25-dihydroxyvitamin D and proximal tubular phosphate reabsorption. Excessive actions of FG23 result in several kinds of hypophosphatemic rickets/osteomalacia including X-linked hypophosphatemic rickets (XLH) and tumor-induced osteomalacia. While neutral phosphate and active vitamin D are standard therapies for child patients with XLH, these medications have several limitations both in their effects and adverse events. Several approaches that inhibit FGF23 actions including anti-FGF23 antibodies and several inhibitors of FGF signaling have been shown to improve phenotypes of model mice for FG23-related hypophosphatemic diseases. In addition, clinical trials indicated that a humanized anti-FGF23 antibody increased serum phosphate and improved quality of life in patients with XLH. Furthermore, circulatory FGF23 is high in patients with chronic kidney disease (CKD). Many epidemiological studies indicated the association between high FGF23 levels and various adverse events especially in patients with CKD. However, it is not known whether the inhibition of FGF23 activities in patients with CKD is beneficial for these patients. In this review, recent findings concerning the modulation of FGF23 activities are discussed.